2017
DOI: 10.1128/iai.00338-17
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes and Shigella flexneri Activate the NLRP1B Inflammasome

Abstract: Activation of the innate immune receptor NLRP1B leads to the formation of an inflammasome, which induces autoproteolytic processing of pro-caspase-1, and ultimately to the release of inflammatory cytokines and to the execution of pyroptosis. One of the signals to which NLRP1B responds is metabolic stress that occurs in cells deprived of glucose or treated with metabolic inhibitors. NLRP1B might therefore sense microbial infection, as intracellular pathogens such as Listeria monocytogenes and Shigella flexneri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…In addition, bacterial DNA released upon cytosolic lysis of L. monocytogenes activates the AIM2 inflammasome [54,55]. More recently, L. monocytogenes was proposed to activate the NLRP1B inflammasome, via causing energy stress in fibroblasts and macrophages [56]. It is thought that L. monocytogenes maintains a low-level of inflammasome activation in order to establish a successful infection.…”
Section: Pathogens Differentially Interfere With the Inflammasomes Anmentioning
confidence: 99%
“…In addition, bacterial DNA released upon cytosolic lysis of L. monocytogenes activates the AIM2 inflammasome [54,55]. More recently, L. monocytogenes was proposed to activate the NLRP1B inflammasome, via causing energy stress in fibroblasts and macrophages [56]. It is thought that L. monocytogenes maintains a low-level of inflammasome activation in order to establish a successful infection.…”
Section: Pathogens Differentially Interfere With the Inflammasomes Anmentioning
confidence: 99%
“…60 RAW 264.7 cells were derived from BALB/c mice, which express NLRP1B allele 1 and do not express NLRP1A. 16,61 Okondo et al 60 15 Surprisingly, CARD8, and not hNLRP1, was found to mediate VbP-induced pyroptosis in these cells, 15 identifying CARD8 for the first time as an inflammasome-forming PRR.…”
Section: The D Ipep Tidyl Pep Tida S E S 8 and 9 (D Pp8/9)mentioning
confidence: 99%
“…Mogridge and co-workers, noting the link between infectious disease and host metabolism, investigated the relationship between energy stress and NLRP1B activation. 61,70,71 Liao et al 70 T gondii and DPP8/9 inhibitors, 2DG plus sodium azide activated NLRP1B without direct N-terminal cleavage. 70,71 Although the molecular details leading to NLRP1B activation remain largely unknown, the authors speculated that 2DG plus sodium azide activates NLRP1B via depletion of cytosolic ATP.…”
Section: Me Tabolic Inhib Itor Smentioning
confidence: 99%
See 1 more Smart Citation
“…AIM2 expression requires type I IFN signalling, consistent with which, L. monocytogenes ‐induced inflammasome activation is severely reduced in type I IFN‐receptor deficient ( Ifnar −/− ) macrophages. L. monocytogenes is a poor activator of NLRC4 (Sauer et al, ; Warren et al, ; Sauer et al, ), but can activate NLRP6, caspase‐11 (Hara et al, ) and NLRP1B (Neiman‐Zenevich et al, ) in mouse macrophages, and NLRP3 in mouse bone‐marrow derived DCs (Clark, Schmidt, McDermott, & Lenz, ). Most L. monocytogenes strains turn down flagellin expression at 37°C and thus evade detection by TLR5 and the NAIP5‐NLRC4 pathway (Theisen & Sauer, ).…”
Section: Monocytogenes Benefits From Inflammasome Activationmentioning
confidence: 99%